SIMULATING THE EFECT OF CAMERA LENS IN COMPUTER GENERATED PICTURE - Hartanto, Budi; Rosalina, Silvia (Institute of Research and Community Outreach - Petra Christian University, 2006)
Original ray tracing method can be used to create picture of objects that are very similar to photographic. However for simplicity, the method mimics a pinhole camera in its model. In pinhole camera all objects visualized in the image generated will be seen sharp. In some cases, this kind of image is acceptable but in other cases it is not. For example, in the movie industry, sometimes it is preferable to get the image that can be focused to a certain object and not to all objects. This effect occurs due to the usage of a lens in a camera. In order to get the same effect to the real camera, then it is necessary to modify the original ray tracing method to use lens in its model. The research performed here has successfully simulating the effect of lens in camera. Therefore only objects that are placed in the lens focus will be seen sharp while the others will become blurry.